Renal Juxtaglomerular Cell Tumors Exhibit Distinct Genomic and Epigenomic Features and Lack Recurrent Gene Fusions: Comprehensive Molecular Analysis of a Multi-institutional Series - Michalova, Kvetoslava; Martinek, Petr; Mezencev, Roman; Gupta, Sounak; Williamson, Sean; Wasco, Matthew; Mohanty, Sambit; Magi-Galluzzi, Cristina; Cañete-Portillo, Sofia; Aron, Manju; Kandukuri, Shivani; Lobo, João; et al. (The American journal of surgical pathology, 2025)
Juxtaglomerular cell tumor (JxGCT) is a rare type of renal neoplasm demonstrating morphologic overlap with some mesenchymal tumors such as glomus tumor (GT) and solitary fibrous tumor (SFT). Its oncogenic drivers remain elusive, and only a few cases have been analyzed with modern molecular techniques. In prior studies, loss of chromosomes 9 and 11 appeared to be recurrent. Recently, whole-genome analysis identified alterations involving genes of MAPK-RAS pathway in a subset, but no major pathogenic alterations have been discovered in prior whole transcriptome analyses. Considering the limited understanding of the molecular features of JxGCTs, we sought to assess a collaborative series with a multiomic approach to further define the molecular characteristics of this entity. Fifteen tumors morphologically compatible with JxGCTs were evaluated using immunohistochemistry for renin, single-nucleotide polymorphism array (SNP), low-pass whole-genome sequencing, and RNA sequencing (fusion assay). In addition, methylation analysis comparing JxGCT, GT, and SFT was performed. All cases tested with renin (n=11) showed positive staining. Multiple chromosomal abnormalities were identified in all cases analyzed (n=8), with gains of chromosomes 1p, 10, 17, and 19 and losses of chromosomes 9, 11, and 21 being recurrent. A pathogenic HRAS mutation was identified in one case as part of the SNP array analysis. Thirteen tumors were analyzed by RNA sequencing, with 2 revealing in-frame gene fusions: TFG::GPR128 (interpreted as stochastic) and NAB2::STAT6 . The latter, originally diagnosed as JxGCT, was reclassified as SFT and excluded from the series. No fusions were detected in the remaining 11 cases; of note, no case harbored NOTCH fusions previously described in GT. Genomic methylation analysis showed that JxGCT, GT, and SFT form separate clusters, confirming that JxGCT represents a distinct entity (ie, different from GT). The results of our study show that JxGCTs are a distinct tumor type with a recurrent pattern of chromosomal imbalances that may play a role in oncogenesis, with MAPK-RAS pathway activation being likely a driver in a relatively small subset.
Keywords: senioři; juxtaglomerulární aparát; jednonukleotidový polymorfismus; epigeneze genetická; lidé; Epigenesis, Genetic; imunohistochemie; Middle Aged; mužské pohlaví; Adult; Kidney Neoplasms; Gene Fusion; Biomarkers, Tumor; Juxtaglomerular Apparatus; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; metylace DNA; lidé středního věku; DNA Methylation; fúze genů; dospělí; Female; Aged; nádory ledvin; Male; Polymorphism, Single Nucleotide